Association Between Short-, Intermediate-, and Long-term Mortality and Myocardial Injury After Noncardiac Surgery After Hip Fracture Surgery: A Retrospective Cohort. (October 2021) - Vacheron, Charles-Hervé; Hentzen, Julie; Fauvernier, Mathieu; Fessy, Michel; Chaudier, Philippe; Landel, Verena; David, Jean Stephane; Incagnoli, Pascal; Piriou, Vincent; Friggeri, Arnaud
Abstract : BACKGROUND: For more than 20 years, hip fracture 1-year mortality has remained around 20%. An elevation of the postoperative troponin peak within 72 hours (myocardial injury after noncardiac surgery [MINS]) is associated with a greater risk of short-term mortality in the general population. However, there seem to be conflicting results in the specific population who undergo hip fracture surgery, with some studies finding an association between troponin and mortality and some not. The objective of the present study was to investigate the association of MINS and the short- (before 28th day), intermediate- (before 180th day), and long-term (before 365th day) mortality after hip fracture surgery. METHODS: We conducted a single-center retrospective cohort of patients undergoing hip fracture surgery from November 2013 to December 2015. MINS was defined as postoperative troponin peak within the 72 hours >5 ng/L. Four MINS subgroups were defined according to the value of troponin peak (ie, ≥5–<20, ≥20–<65, ≥65–<1000, and ≥1000 ng/L). To document the association between the different mortality terms and the troponin peak, odds ratio (OR) and adjusted OR (aOR) associated with their 95% confidence interval (CI) with the log of the scaled troponin peak within 72 hours were estimated, with and without patients presenting a postoperative acute coronary syndrome (ACS). Cox proportional hazards modeling was used to estimate hazard ratio (HR) and adjusted HR (aHR) of death between the no MINS and MINS subgroups. The adjustment was performed on the main confounding factors (ie, sex, American Society of Anesthesiologists [ASA] physical status, dementia status, age, and time from admission to surgery). RESULTS: Among 729 participants, the mean age was 83.1 (standard deviation [SD] = 10.8) years, and 77.4% were women; 30 patients presented an ACS (4%). Short-, intermediate-, and long-term mortality were at 5%, 16%, and 23%, respectively. The troponin peak was significantly associated with all terms of mortality before and after adjustment and before and after exclusion of patients presenting an ACS. HR and aHR for each subgroup of troponin level were significantly associated with an increased probability of survival, except for the 5 to 20 ng/L group for which aHR was not significant (1.75, 95% CI, 0.82-3.74). In the landmark analysis, there was still an association between survival at the 365th day and troponin peak after the short- and intermediate-term truncated mortality. CONCLUSIONS: MINS is associated with short-, intermediate-, and long-term mortality after hip fracture surgery. This could be a valuable indicator to determine the population at high risk of mortality that could benefit from targeted prevention and possible intervention.